Sodium Zirconium Cyclosilicate in the Gastrointestinal Tract Mimicking an Acute Gastrointestinal Bleed on CT - John J. Hines; Joshua Roberts; Douglas S. Katz (Reports)
Hyperattenuating contents detected in the gastrointestinal (GI) tract on CT scans are commonly seen and are almost always due to the purposeful ingestion of an oral contrast agent, usually barium- or iodine-based, used for evaluating the GI tract. Occasionally, other ingested material such as antacids or other medications, foreign objects, and medical devices can also be hyperattenuating. While these are usually correctly identified, these materials can potentially be misdiagnosed as a pathologic condition. Lokelma (sodium zirconium cyclosilicate (SZC)) is an increasingly used agent to treat hyperkalemia and has a hyperattenuating appearance on CT due to the presence of zirconium. However, this is not well known to the radiologic community. Here, we describe a case where SZC was seen in the GI tract on CT and misinterpreted as an acute GI bleed. A 72-year-old woman underwent single (portal venous) phase intravenous contrast-enhanced abdominal and pelvic CT after presenting to the ED with a lower GI bleed. The CT showed intraluminal hyperattenuation within the cecum, which was diagnosed prospectively as an active GI bleed. A CT angiogram of the abdomen and pelvis performed the following day for follow-up showed the hyperattenuating contents to be present on the non-IV contrast-enhanced series of the study, thereby proving that it was not due to active bleeding. Further investigation of the patient’s medical record showed that the patient was being treated with SZC for hyperkalemia, accounting for the hyperattenuating cecal contents. Awareness of the hyperattenuating appearance of SZC on CT by radiologists and clinical staff can help avoid confusion and misdiagnosis.